2021
DOI: 10.3389/fgene.2021.746060
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 Mutation Spectrum and Natural History of ALS Patients in a 15-Year Cohort in Southeastern China

Abstract: Background: Mutations in superoxide dismutase 1 gene (SOD1) are the most frequent high penetrant genetic cause for amyotrophic lateral sclerosis (ALS) in the Chinese population. A detailed natural history of SOD1-mutated ALS patients will provide key information for ongoing genetic clinical trials.Methods: We screened for SOD1 mutations using whole exome sequencing (WES) in Chinese ALS cases from 2017 to 2021. Functional studies were then performed to confirm the pathogenicity of novel variants. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Among the ALS patients, nearly 90%–95% belong to sporadic ALS (sALS) most with unknown etiology 2 , while approximately 5%–10% is familial ALS (fALS) 3 associated with known gene mutations. Cu/Zn superoxide dismutase 1 (SOD1) is the leading cause for ALS in China, and account for 25.3% of Chinese fALS cases 4 , 5 . Although a number of candidates have been shown to delay disease progression in preclinical trials, riluzole and edaravone are only two drugs approved by US Food and Drug Administration for ALS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ALS patients, nearly 90%–95% belong to sporadic ALS (sALS) most with unknown etiology 2 , while approximately 5%–10% is familial ALS (fALS) 3 associated with known gene mutations. Cu/Zn superoxide dismutase 1 (SOD1) is the leading cause for ALS in China, and account for 25.3% of Chinese fALS cases 4 , 5 . Although a number of candidates have been shown to delay disease progression in preclinical trials, riluzole and edaravone are only two drugs approved by US Food and Drug Administration for ALS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the clinical phenotype and prognosis of FALS harboring mutant SOD1 were closely related to the mutated site of the gene 20 . Most SOD1 mutations are heterozygous, but there have been reports that homozygous SOD1 mutations showed juvenile-onset and rapid progression, such as a French case of FALS harboring SOD1-L84F mutation 21 , a juvenile-onset Pakistani case of FALS harboring SOD1-N86S 22 , and a Japanese case of FALS carrying SOD1-L126S 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential mechanisms of the toxicity of mutated SOD1 in motor neurons are still not fully understood, the SOD1 gene itself marked the beginning of a new era of research on ALS. This is due to the fact that it was used to create the first SOD1-G93A transgenic mice model, which is still used in clinical trials [ 79 , 87 , 88 , 89 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%